Sensitivity, Specificity and Accuracy of Androgen Deficiency in Ageing Male (ADAM) Questionnaire for the Clinical Detection of Androgen Deficiency in the Male Population in Pakistan - Naz, Sidra (Cureus, 2020)
Introduction: Androgen deficiency in relation to the increasing age is quite prevalent worldwide. However, diagnosing it in low-income countries is quite a challenge due to cost concerns. Through this study, we plan to measure the sensitivity and specificity of the Androgen Deficiency in Ageing Male (ADAM) questionnaire in the Pakistani population. Methods: A cross-sectional survey study was conducted from September 2019 to November 2019 in a Pakistani tertiary care hospital. Two hundred and fifty-five participants belonging to ages 30-69 years completed the ADAM Questionnaire in the out-patient department. Venous blood samples were taken to check serum total testosterone levels. Results: The ADAM questionnaire revealed 90.12% sensitivity, 41.3% specificity, 45.34% positive predictive value, 90.80% negative predictive value, and 61.29% accuracy in the Pakistani population. Conclusion: Low specificity and positive predictive value have been shown by the ADAM questionnaire. Hence, it cannot be used as a diagnostic tool to detect androgen deficiency, replacing the blood sample.